2018
DOI: 10.1021/acssynbio.8b00273
|View full text |Cite
|
Sign up to set email alerts
|

Retroelement-Based Genome Editing and Evolution

Abstract: While several genome editing methods exist, few are suitable for the continuous evolution of targeted sequences.Here we develop bacterial retroelements known as "retrons" for the dynamic, in vivo editing and mutagenesis of targeted genes. We first optimized retrons' ability to introduce preprogrammed mutations, optimizing both their expression and the host machinery that interacts with them to increase the incorporation frequency of mutations 78-fold over rates previously reported in synthetic systems. The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 72 publications
2
46
0
Order By: Relevance
“…However, the sequences and lengths of the reverse transcribed template significantly vary and frequently show no sequence similarity between retrons 7 . The ability of retrons to produce ssDNA in situ has been adapted for multiple applications of synthetic biology and genome engineering 5,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the sequences and lengths of the reverse transcribed template significantly vary and frequently show no sequence similarity between retrons 7 . The ability of retrons to produce ssDNA in situ has been adapted for multiple applications of synthetic biology and genome engineering 5,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies have demonstrated that inactivation of exonucleases improves oligonucleotide recombineering by up to 3-fold 20,21 , and this effect has been shown for retron recombineering as well 22,23 . Inactivation of exonuclease genes recJ or sbcB (also known as xonA ) individually provided benefit, and inactivation of both together increased the fraction of genomes edited during induction of retron recombineering in batch growth by 131 and 201-fold for the gyrA and rpoB donors, respectively (Fig 2B, S1C).…”
Section: Resultsmentioning
confidence: 80%
“…First, we varied the conditions that affect the efficiency of homologous recombination. The effects of changing the length of msd (from 55 to 115 bp) 18, 22 and the presence/absence of Beta recombinase 13, 14 (which stabilizes ssDNA) were tested; optimal efficiency was obtained with an msd length of 95 bp and co-expression of Beta recombinase ( Figure 2d, e ). We then examined the effect of varying conditions related to selection pressure using the CRISPR/Cas9 system.…”
Section: Resultsmentioning
confidence: 99%
“…Unedited cells can be problematic because their presence can interfere with interpretation when the screening process is not based on chemical selection. Enhancing the recombineering machinery via knock-out of exonucleases 14 , for example, could help reduce the proportion of unedited cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation